ICE Dispute Resolution Board procedure (Thomas Telford, 2005)
Dispute Resolution Boards (DRB)s are a form of dispute avoidance and resolution. DRBs have proven an effective, economic and user-friendly method of avoiding the extensive costs and diversions of resources usually associated with dispute resolution in the construction and engineering industries. Usually consisting of three experienced, respected and independent Adjudicators, the DRB is the generic phrase used to include Dispute Adjudication Boards, Dispute Review Boards and Panels and Dispute Conciliation Boards.
Keywords: Labor disputes -- Great Britain.; Construction industry -- Great Britain -- Employees.; elektronické knihy; electronic books